Discretionary Trading and Asset Price Volatility - Aziz, Jahangir (IMF Working Papers; Working Paper ;, 1995)
The IMF Working Papers series is designed to make IMF staff research available to a wide audience. Almost 300 Working Papers are released each year, covering a wide range of theoretical and analytical topics, including balance of payments, monetary and fiscal issues, global liquidity, and national and international economic developments.